Corrigendum to: “Effect of ginger extract and/or fenofibrate on the associated infertility of experimentally induced obese Wistar Albino male rats” [Reprod Biol 26 (2): 101208] - Mohamed H. Elsayed; Samia M. Abd El-Rheem; Essam A. Almadaly; Azza M. Elkattawy; Nasr EL. Nasr; Doaa A. Dorghamm; Walied S. Abdo; Mona Assas; Tarek K. Abouzed; Wael B. El-Domany (Reproductive Biology, 2026)

Effect of ginger extract and/or fenofibrate on the associated infertility of experimentally induced obese Wistar Albino male rats - Mohamed H. Elsayed; Samia M. Abd El-Rheem; Essam A. Almadaly; Azza M. Elkattawy; Nasr EL. Nasr; Doaa A. Dorghamm; Walied S. Abdo; Mona Assas; Tarek K. Abouzed; Wael B. El-Domany (Reproductive Biology, 2026)

The post-thaw quality, antioxidant activity, and in vivo fertility of Zaraibi buck semen frozen-stored in the presence of different concentrations of either quercetin or L-arginine - Essam A. Almadaly; Mohamed A. Elbendary; Samia M. Abd El-Rheem; Ahmed M. Shehabeldin; Wael B. El-Domany; Adel A. Ramoun (Cryobiology, 2026)

Implication of apoptosis and oxidative stress in mitigation of ivermectin long-term hazards by zinc nanoparticles in male rabbits - Set A. El-Shobokshy; Magda I. Abo-Samaha; Ferial M. Sahwan; Samia M. Abd El-Rheem; Mohamed Emam; Asmaa F. Khafaga (Environmental Science and Pollution Research, 2022)
Ivermectin is the medication of choice for treating human onchocerciasis and is used in veterinary medicine to treat a variety of ectoparasites and endoparasites. This study was designed to investigate the effects of zinc nanoparticles (ZnNPs) on the fertility of male rabbits exposed to experimental ivermectin (IVM) intoxication. A total of 72 mature male rabbits were equally divided into 4 groups ( n = 18). The first group (CTR) served as control; the second group (IVM) received subcutaneous injection of IVM (0.2 mg/kg body weight); the third group (ZnNPs) fed on zinc nanoparticles (60 mg/kg diet); and the fourth group (ZnNPs + IVM) were administered IVM and zinc nanoparticles at the same doses. The experiment lasted for 9 weeks. Results revealed that IVM-intoxicated rabbits showed impaired growth performance parameters, including body weight, total body weight gain (TBWG), total feed intake (TFI), and feed conversion ratio (FCR). Moreover, carcass characteristic and fertility parameters (including semen quality parameters and testosterone levels) were also impaired after IVM administration. Additionally, testicular malondialdehyde (MDA) and antioxidant (reduced glutathione, superoxide dismutase, catalase) levels as well as the histopathology and immunohistochemical expression of caspase 3 and PCNA in the testes and epididymis were detrimentally affected. On the contrary, ZnNP administration efficiently improved most of these parameters in IVM-intoxicated rabbits. In conclusion, ZnNPs exhibited promising ability for improving the growth and fertility status of rabbits and reducing the deleterious effects of IVM possibly through the suppression of apoptotic and oxidative pathways. Graphical Abstract